Nematoda Parasit Pada Rattus spp. dari Pulau Simeulue, Aceh - Muhammad F. Musyaffa; Kartika Dewi; Nanang Supriatna; Moch. Irfan Hadi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
Rattus spp. are often found living together in the human environment. Till date, there are no data on nematodes in rats from Simeulue Island. Therefore, a research on the nematodes of Rattus spp. from Simeulue Island, Aceh was conducted to know the species and the pattern of nematodes infection. The observation was carried out by dissecting 14 carcasses of Rattus spp. and then observing the internal organs for nematodes. For the result, we identified four species i.e., Syphacia muris, Cyclodontostomum purvisi, Gongylonema neoplasticum, and Nippostrongylus brasiliensis with prevalence 28.5%, 7.1%, 7.1%, 85.7%, respectively, and parasite indexes 1-23, 1, 1, 2-118 individual parasites in each host, respectively.Key words: nematodes, parasites, Rattus spp., Simeuleu Island.